PENGGUNAAN RISET OLEH PRAKTISI PUBLIC RELATIONS DALAM MENENTUKAN PROGRAM - nilam wardasari (Jurnal Nomosleca, 2018)
AbstractThe need for a positive public image is a need for all agencies. These needs make public relations practitioners are required to actively create programs. The expected program is certainly a program that can meet the needs or solve public problems. Lumoindong and Wullur (2016) research results show that if the goals in the program implementation are not achieved, the program will fail. While the achievement of the objectives of the public relations program is based on the findings at the stage of defining the problem. The process of defining the problem in cutlip, center broom (2007, p. 321) is called research. This study aims to find out how to use research in public relations practitioners in 3 different types of agencies. This research uses a qualitative approach with descriptive type. Data collection techniques in the form of interviews and documentation. Data analysis technique used is the filling system technique as stated by Wimmer and Dominick (2011) in the form of data collection, data categorization and analysis with theories and concepts. The informant selection technique used is purposive sampling. Informants in this study are 1) Executive Chairman of Shebs PR Empire Malaysia), Atria Hotel Public Relations Malang and Public Relations Faculty of Social and Political Sciences, Brawijaya University Malang. The results of this study indicate if the characteristics and internal policies of agencies determine the type and purpose of research conducted by public relations practitioners.Keywords: Research, Public relations practitioners, ProgramsDOI : https://doi.org/10.26905/nomosleca.v4i2.2375